Randomized clinical study using xenograft blocks loaded with bone morphogenetic protein‐2 or autogenous bone blocks for ridge augmentation – A three‐dimensional analysis. Issue 9 (24th June 2019) - Thoma, Daniel S.; Bienz, Stefan P.; Payer, Michael; Hüsler, Jürg; Schmidlin, Patrick R.; Hämmerle, Christoph H. F.; Jakse, Norbert; Jung, Ronald E.
Abstract: Objectives: To test whether or not the use of a xenogeneic block loaded with rhBMP‐2 results in superior radiological and profilometric outcomes compared to an autogenous bone block. Materials and methods: Twenty‐four patients randomly received a xenogeneic block loaded with rhBMP‐2 (test) or an autogenous bone block (control) for primary augmentation. The ridge width (RW) was evaluated by means of a CBCT scan after augmentation surgery and at 4 months, prior to implant placement. Surface scans were taken prior to augmentation and at 4 months for profilometric analyses. Data were analyzed with Wilcoxon‐signed rank test, Mann–Whitney test, or nonparametric ANOVA models. Results: The median RW after augmentation amounted to 7.13 mm (Q1 = 6.02; Q3 = 8.47) for test and 6.86 mm (Q1 = 5.99; Q3 = 8.95) for control. During 4 months of healing, the total RW decreased statistically significantly and measured 5.35 mm (Q1 = 4.53; Q3 = 6.7) for test and 5.15 mm (Q1 = 3.57; Q3 = 7.24) for control ( p = 0.0005). The differences between the groups were not statistically significant ( p > 0.5899). The buccal soft tissue contour slightly increased for test (0.83 mm; Q1 = 0.62; Q3 = 1.87) and control (1.16 mm; Q1 = 0.50; Q3 = 1.44). Conclusions: Both treatment modalities successfully increased the ridge width to a similar extent. The shrinkage during healing was not greater in the test than in the control group. The impact of hard tissue augmentation on the soft tissue contour was, however, minimal.